Legal Challenges to Local Communities' Land Rights in the Capital City of Nusantara - Rahmawati Al Hidayah; Aryo Subroto; Setiyo Utomo (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze land policies before and after the establishment of the National Capital City (IKN), including regulations on restrictions or freezes on land rights transfers, as well as regulations on land acquisition, and their impact on local communities, both indigenous and non-indigenous. The method used is an empirical legal approach or socio-legal studies that focus not only on norms but also on the context of their enforcement in the IKN area, particularly in North Penajam Paser Regency. This is done by analyzing facts in the field related to land regulations in the IKN area, which directly impact local communities. The novelty of this research lies in the dynamics of regulations issued before and after the establishment of the IKN, particularly in terms of land, ranging from the freezing of transfer of rights to land acquisition for the development of the IKN, which has implications for conflicts over the living space of local communities. The results of this study found that the land regulations that have been in place since the establishment of the IKN have had an impact on the control and use of community land, where conflicts have been triggered by the lack of transparency in the development process, compensation issues, and the suspension of land rights registration. The concluded that land regulations related to the development of the IKN have an impact on the control and use of land by local communities. Legal efforts to resolve land tenure issues in the IKN need to be differentiated based on when the issues arose. Problems that occurred before the establishment of the IKN should be resolved through non-litigation efforts such as negotiation and mediation, while post-establishment IKN issues should be addressed by adjusting the implementation of the land acquisition scheme to the existing conditions in the field.